Comparación entre dexmedetomidina versus midazolam en pacientes con anestesia raquídea. - Arguello Rodríguez, María Fernanda (2015)
The sedation as a complement to the spinal anesthesia reduces ansiety, it avoids the remembrance of pain ful events, it also models hemodynamic effects and it keeps verbal capacity ability to communicate, over call this study proposes how to compare the sedating level in the Ramsay scale, produced by each one of these type of medice Dexmedetomidine and Midazolam in patients under spinal anesthesia. Determing which medice produces less lack of hemodynamic stability; which medice produces less respiratory depression which medice produces the best sedating level during surgery as well as which medice produces the best sedating level post surgery.This study is formed by 60 patients, among men and women from 18 to 80 years old, put though surgical procedures under spinal anesthesia, from which 30 patients received Midazolam IV and another 30 received Dexmedetomidine IV through fluid. A data base was use for research record which included the Ramsay scale to evaluate the sedating level in patients during surgery, the heart rate record, medium blood pressure and the saturation level of oxygen during surgery and the Ramsay sedating scale to evaluate the sedating level in a patient during surgery. The first group of patients had 1mg to 1,5 mg IV of Midazolam, and the second group had a first doze of 1 ug/kg of Dexmedetomidine through an IV fluid during the first 15 minutes and later on had a second doze of 0,3 ug/kg/h for mainance. The data was taken once the spinal blockage was proven, and that’s when both medicines were administrated, data which was taken every 15 minutes during surgery and 30 minutes after surgery. Through the descriptive t student analysis, it was shown that the group that received Dexmedetomidine produced a sedating level 2 in the Ramsay scale during surgery in most of the cases, on the other hand the group the received Midazolam produced a sedating level between 2 a 3 in the Ramsay scale during surgery in most cases. It was also found that Midazolam produces a decreased level on a medium blood pressure which is slighty higher than the decrease produce by Dexmedetomidine during surgery which also produces a slight decrease on heart rate 45 minutes in to surgery. While Dexmedetomidine produced a heart rate decreased of 15 to 45 minute producing a low heart level of 60 heart beats per minutes, 30 minutes in to surgery in most cases. Midazolam also produce a decreased level of oxygen saturation during surgery in most cases, while Dexmedetomidine kept the saturation level of oxygen between 95% and 97% in most cases. We can conclude that Dexmedetomidine has a higher hemodynamic stability than Midazolam which produces a level higher level of medium blood preassure being decreased with a slight heart rate increment. Unlike Midazolam, Dexmedetomidine doesn´t causa low oxygen levels with saturations higher than 95%, which decreases oxygen to be saturated in most cases and it can cause low oxygen levels on geriatric patients with respiratory pathologies, since Dexmedetomidine produces better sedating levels in the Ramsay scale than Midazolam during surgery and a better sedating level in the Ramsay scale after surgery. Key words: Midazolam, Dexmedetomidine, saturation, heart rate.